Penja Fish Flour Cookies: Nutritional Composition and Sensory Acceptability as a Local Food-Based Intervention for Child Undernutrition - Septiyanti, Septiyanti; Patimah, Sitti; Bur, Nurfardiansyah (Journal of Health and Nutrition Research, 2025)
West Sulawesi has a high prevalence of underweight among toddlers, recorded at 22.5% in the 2022 Indonesian Nutritional Status Survey (SSGI). Penja fish, a local food with higher protein content than anchovies, offers potential as a supplementary food (PMT) for addressing child undernutrition. However, its traditional use remains limited to salting and direct consumption. Processing penja fish into flour for cookies provides a sustainable, innovative strategy to diversify intake and mitigate seasonal supply challenges. This experimental study, employing a post-test only control group design, aimed to assess the nutrient composition and acceptability of cookies with varying levels (0%, 25%, 50%, 75%, and 100%) of penja fish flour substitution. Research was conducted between September and November 2024 across laboratories at Universitas Hasanuddin and Universitas Muslim Indonesia. Nutritional analyses included proximate composition, and acceptability was measured through hedonic testing. Significant differences were found across formulations in color, aroma, texture, and taste (p < 0.001). Cookies containing 25% penja fish flour (Formula B) were the most preferred, with a proximate composition of 9.83% protein, 29.39% fat, 54.45% carbohydrates, 2.04% ash, and 5.30% moisture. Penja fish flour substitution enhanced the nutritional profile and acceptability of cookies. Formula B meets the nutritional requirements for supplementary feeding programs targeting underweight toddlers.